Kamisama kiss. Vol. 15 - Suzuki, Julietta (Shojo beat manga., 2014)
""Nanami Momozono is alone and homeless after her dad skips town to evade his gambling debts and the debt collectors kick her out of her apartment. So when a man she's just saved from a dog offers her his home, she jumps at the opportunity. But it turns out that his place is a shrine, and Nanami has unwittingly taken over his job as a local deity! Nanami has gone back in time in order to find the fallen kami who cursed Tomoe, but the past is a lot more violent than she expected. Before she can even start her search, she has to deal with suspicious villagers and a mortally wounded Tomoe!"--